Framing Illegal Logging and Its Governance Responses in Brazil – A Structured Review of Diagnosis and Prognosis - Kleinschmit, Daniela; Ferraz Ziegert, Rafaella; Walther, Laura (Frontiers in Forests and Global Change, 2021)
In 2012, the new, revised Forest Code was established as the legal and regulatory framework for Brazilian forests. Though illegal logging has continued, frames about Brazil's forest policy and management have changed since that time. While until 2010 the successful implementation of forest policies and the resulting decline in deforestation rates were there for all to see and appreciate, the increase in the deforestation rate since then has become the focus of international criticism. With the help of a structured review of international scientific literature, newspaper articles, and programmes initiated by non-governmental organizations' (NGO) and international organizations' (IO), this paper aims to analyse the frames of illegal logging and its governance responses in Brazil since 2012. The review is guided by the framework of diagnostic (What is the problem? Who is to blame?) and prognostic framing (proposed policy and governance solutions). The main findings revealed a master frame of environmental justice that combines injustice toward indigenous people with the victimization of forest and environment at large. Embedded in this master frame, specific frames that follow the institutional logic of the single policy discourses have been identified. Finally, the results show a strong national focus of governance with continued emphasis on command and control instruments.